Pengaruh Penambahan Cetyltrimethylammonium Bromide (CTAB) pada Silika dari Natrium Silikat (Na2SiO3) - Habibur Rahman Dafnaz; Budhi Oktavia; Hardeli Hardeli; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2022)
Silica is a useful material in adsorption, electronics, mechanical, medical, art to other fields. In this study, Sodium silicate is used which can be used as a more economical precursor of silica as which is produced from natural silica. Silica was synthesized using the sol-gel method. This study aims to determine the effect of adding CTAB mass and aging time in synthesizing silica. The synthesized silica was tested for iodine absorption value and characterized using FTIR. Based on the iodine absorption of variations in adding mass CTAB (0,1, 0,15, 0,2, 0,25, and 0,3 gram) and aging time (8, 12, 16, 20 and 24 hours) give the most absorption to optimum conditions of adding mass CTAB at 0,2 gram and aging time at 16 hours. The results of measurements with FTIR showed the presence of absorption bands which indicated the loss of CTAB in the synthesized silica.